Enhanced efficiency of Cu2ZnSn(S, Se)4 solar cells via anti-reflectance properties and surface passivation by atomic layer deposited aluminum oxide. Issue 34 (24th May 2018) - Zhang, Bingye; Han, Lu; Ying, Shitian; Li, Yongfeng; Yao, Bin
Abstract : ALD-Al2 O3 is used as a passivation layer in a CZTSSe device and optimal device parameters are obtained by precisely controlling Al2 O3 thickness. Abstract : Reducing interface recombination losses is one of the major challenges in developing Cu2 ZnSn(S, Se)4 (CZTSSe) solar cells. Here, we propose a CZTSSe solar cell with an atomic layer deposited Al2 O3 thin film for surface passivation. The influence of passivation layer thickness on the power conversion efficiency (PCE), short-circuit current density ( J sc ), open-circuit voltage ( V oc ) and fill factor (FF) of the solar cell is systematically investigated. It is found that the Al2 O3 film presents notable antireflection (AR) properties over a broad range of wavelengths (350–1000 nm) for CZTSSe solar cells. With increasing Al2 O3 thickness (1–10 nm), the average reflectance of the CZTSSe film decreases from 12.9% to 9.6%, compared with the average reflectance of 13.6% for the CZTSSe film without Al2 O3 . The Al2 O3 passivation layer also contributes to suppressed surface recombination and enhanced carrier separation. Passivation performance is related to chemical and field effect passivation, which is due to released H atoms from the Al–OH bonds and the formation of Al vacancies and O interstitials within Al2 O3 films. Therefore, the J sc and V oc of the CZTSSe solar cell with 2 nm-Al2 O3 were increased by 37.8% and 57.8%, respectively, in comparison with those of the unpassivated sample. An optimal CZTSSe solar cell was obtained with a V oc, J sc and η of 0.361 V, 33.78 mA and 5.66%. Our results indicate that Al2 O3 films show the dual functions of AR and surface passivation for photovoltaic applications.